Problematika Wakaf dan Penyelesaiannya di Pesantren Al-Falah Limboto Barat Kabupaten Gorontalo - Tarnima Zakiyah Rini; Abdur Rahman Adi Saputera Putra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2020)
This study aims to uncover the problem of waqf and its solution at Pesantren Al-Falah Limboto Gorontalo. This research is field research, which is descriptive of analytical with the primer data and sekunder data. The data collection techniques used in this study are observation, interview, and documentation. While data analysis techniques include: data reduction, display, conclusions, and verification. The results showed that the procedure for the implementation of waqf at the Al-Falah Islamic Boarding School was originally carried out based on the principle of mutual trust without any element of doubt in the future it will cause problems. So that the agreement to hand over the donated land was not carried out. The path taken in resolving waqf disputes at the Al-Falah Islamic Boarding School is by deliberation or underhand. As for every heir who is deemed less capable of receiving mercy from the boarding school.